To complete the square we:
Move the non-x tern to the right x^2 + 6c = 12
Divide the equation by the coefficient of x^2 (already done)
Next we take the coefficient of x, divide it by 2, square it, then add it to both sides.
6 / 2 = 3 then 3^2 = 9 then adding to both sides
x^2 + 6x + 9 = 12 +9
(x+3)^2 = 21 then taking the square root of both sides:
x + 3 = square root (21)
x = square root (21) -3 equals 4.582575695 -3
x1 = 1.582575695
AND remebering the square root (21) also = -4.582575695 then
x2 = -7.582575695
Source: 1728.com/quadr2.htm